Plant Connections Leader's Guide - Janice Easton; Deborah J. Glauer (EDIS, 2015)
This revised 195-page curriculum guide is aimed at educating youth about the basics of horticulture. Youth will be exposed to information on plants and the plant kingdom. Written by Janice Easton and Deborah J. Glauer, and published by the UF Department of 4-H Youth Development, January 2015.